Resposta :
Sejam os conjuntos:
A = [2; 7]
B = [-1; 5]
E = [3; 9[
entao:
a) A - B = ]5; 7]
b) B - A = [-1; 2[
c) A - E = [2; 3[
d) E - B = ]5; 9[
em anexo diagrama com mais detalhes
![Ver imagem TOMSON1975](https://pt-static.z-dn.net/files/dfe/ecbf56acf11f8e6d6ee403627d3034b1.png)
![Ver imagem TOMSON1975](https://pt-static.z-dn.net/files/d56/01a5c42f0045167e3f59a30e1173c1fd.png)
Sejam os conjuntos:
A = [2; 7]
B = [-1; 5]
E = [3; 9[
entao:
a) A - B = ]5; 7]
b) B - A = [-1; 2[
c) A - E = [2; 3[
d) E - B = ]5; 9[
em anexo diagrama com mais detalhes